Isolation and Structural Characterization of Anthocyanin-furfuryl Pigments - Andre Sousa (2010)
Condensation reactions of malvidin-3-glucosicle with two representative oak wood furanic aldehydes (furfural and methylfurfural) were conducted in wine-like model solutions. Methylfurfural led to the formation of malvidin-3-glucoside-methylfurfural (603 m/z), whereas furfural led to the formation of malvidin-3-glucoside-furfural (589 m/z). The latter was structurally characterized by 10 and 2D NMR, allowing an elucidation of the formation mechanism of these anthocyanin-furanic aldehyde adducts in the absence of flavanols.